Customer satisfaction mobile phone services: an empirical study on Grameen Phone (GP) and Banglalink (BL) in Bangladesh - Haque, A. K. M. Ahasanul; Nuruzzaman, N; Kalam, Abul (Medwell Journals, 2011)
This study is to examine the satisfaction of customers towars the mobile phone services in Bangladesh based on the Mertin Fishbein's multiattribute attitude model. Some important factors or attributes (i.e., services) of GP and BL that affect the satisfaction level of the customers have been identified where customers give special emphasis. Two leading companies (GP and BL) and nine factors out of 28 have been considered for the convenience of the study. It was examined from the study that customers of Banglalink are more satisfied than the Grameen Phone (GP). Means differences of differents factors for the two companies are measured through t-test for test significance. Outcomes of the study may be used as an index by the mobile phone service providers for improvement of their services to satisfy the customers.